Design of an agent-based framework for processes collaboration in electronic marketplace. (1st January 2003) - Chen, R.-S.; Chen, C.C.; Lin, H.-M.
Specialised business-to-business Internet electronic markets deliver substantial value to companies including greater liquidity, better pricing, and faster transactions. The electronic marketplace sits on the intersection between supply chain and demand chain and makes it the business collaborative platform where resource allocation optimising and efficiency improving occurs simultaneously. The electronic marketplaces can help companies reduce cost structures by accessing stable venues with market pricing to fulfil short-term commodity needs. However, the variances in business processes and data format between trading partners cause overhead cost and time consumption. This paper proposes an agent-based framework to integrate processes between businesses and the electronic marketplace. This framework is composed of workflow systems, collaborative agents, Common Business Language, and electronic marketplace service platform. The business vocabularies and inter-partner processes used to communicate between trading partners are defined as an XML-based format. The result of this framework provides three functions including: (1) process executing; (2) message transforming; and (3) business transactions tracking and management. Trading partners can integrate inter-organisational processes without dramatically rewriting their legacy system.